The Global Micro-credential Landscape: Charting a New Credential Ecology for Lifelong Learning - Mark Brown (Commonwealth of Learning, 2021)
This article offers a global overview of the burgeoning field of micro-credentials and their relationship to lifelong learning, employability and new models of digital education. Although there is no globally accepted definition of micro-credentials, the term indicates smaller units of study, which are usually shorter than traditional forms of accredited learning and courses leading to conventional qualifications such as degrees. The paper aims to provide educators with a helicopter view of the rapidly evolving global micro-credential landscape, with particular relevance to higher education leaders, industry stakeholders and government policy-makers. It addresses five questions: (i) what are micro-credentials? (ii) why micro-credentials? (iii) who are the key stakeholders? (iv) what is happening globally? and (v) what are some of the key takeaways? Drawing on a European-wide perspective and recent developments in The Republic of Ireland, the paper concludes that micro-credentials are likely to become a more established and mature feature of the 21st Century credential ecology over the next five years. While the global micro-credential landscape is currently disconnected across national boundaries, more clarity and coherence will emerge as governments around the world increasingly align new credentialing developments with existing national qualification frameworks. The micro-credentialing movement also provides opportunities for governments and higher education institutions in partnership with industry to harness new digital learning models beyond the pandemic.